(untitled) (Archives of Pediatrics of Uruguay, 2020)
Introduction: polytherapy is a growing concern in the pediatric population: it is defined as the consumption of two or more drugs, since it is associated with an increased risk of side effects. It is necessary to study the broad range of drugs used in this population in order to gain a thorough understanding of the consequences of polytherapy. Objective: describe polytherapy in children and adolescents between 2 and 15 years of age who consume two or more drugs chronically, hospitalized at the moderate care ward of the Pereira Rossell Pediatric Hospital in July-September 2019. Methodology: survey to caregivers of children and adolescents between 2 and 15 years of age who take two or more drugs chronically. The following variables were analyzed: age, sex, groups of drugs, quantity of active ingredients, most frequent combinations, diagnosis, “off-label” prescription, health professional who prescribed the treatment and health professional who monitored it. Results: 82 surveys were carried out, 53 children and 29 adolescents. The consumption of two drugs was predominant for all age ranges and for both sexes. Of a total of 251 drugs recorded, the most frequent were those related to the nervous system (n = 124) followed by those of the respiratory system (n = 71), no significant differences were found regarding sex, however age did show significant differences. 41.25% of the nervous system drug prescriptions were ‘off-label’, while none were off-label for the case of respiratory drugs. Conclusion: psychotropic and anti-asthmatic drugs are the highest consumed in cases of polytherapy. Most of the patients who took psychotropic drugs did not have a previous diagnosis and had frequently been prescribed ‘off-label’ drugs. We note the importance of periodic updates to the national prescription guidelines.